What local scientists write. Text as a social action - Méndez-Arreola, Roberto; Kalman, Judith (Íkala, Revista de Lenguaje y Cultura, 2019)
This paper presents the findings of research work on written reports prepared by members of citizen science endeavor dubbed The Royal Post (Correo Real)in Mexico. Those are documents prepared by citizens committed to record in written Monarch butterfly migration. An ethnographic analysis was performed on five materials chosen from a collection of nearly 300 documents. Interviews were held with their authors, as well as their texts revised in order to identify aspects related to the format and the inscription surface. Analysing written texts allowed us to identify their authors’ aims, as well as the spaces where they were prepared and disseminated. Our main findings suggest that, unlike the re-production of science genres, encouraged in similar efforts —science at school and professional science—, participants at The Royal Post prepare reports that may be classified as scientific reports, letters, activity reports, personal texts, and support requests, challenging the stability and homogeneity of writing done in scientific tasks. These findings lead to discuss the pertinence of considering textual genres as social action, since in producing them, different voices, aims, social languages, and meanings are articulated, but most of all, this shows varied ways to participate in science through plural writing, meaningful for its authors.